Answer:
![\frac{3x}{3 - 2x}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x%7D%7B3%20-%202x%7D%20)
Step-by-step explanation:
Here,
f(x) = y
![y = \frac{3x}{2x + 3}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3x%7D%7B2x%20%2B%203%7D%20)
or , swapping x with y
![x = \frac{3y}{2y + 3}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B3y%7D%7B2y%20%2B%203%7D%20)
now to solve for y we get
![y = \frac{3x}{3 - 2x}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3x%7D%7B3%20-%202x%7D%20)
now we put f inverse x instead of y
![{f}^{ - 1} (x) = \frac{3x}{3 - 2x}](https://tex.z-dn.net/?f=%20%7Bf%7D%5E%7B%20-%201%7D%20%28x%29%20%3D%20%20%5Cfrac%7B3x%7D%7B3%20-%202x%7D%20)
I am done.
Answer:
C) Similar-SAS
Step-by-step explanation:
Here,
BSE ~ TES
Now,
BS = TE (:• being corresponding side )
BSE = TES (:• Being Corresponding angle
SE = SE (:•Being corresponding side)
Therefore,
the given triangle is similar by
SAS axiom
Answer:
That would be sina.
Step-by-step explanation:
sin(a+b) = sinacosb + cosasinb
sin(a-b) = sinacosb - cosasinb
Adding we get sin(a+b) + sin(a-b) = 2sinaccosb
so sinacosb = 1/2sin(a+b) + sin(a-b)
Answer:
51
Step-by-step explanation:
4x12-3x3+12
48-9+12=51